Role of TRPM7 in Cancer: Potential as Molecular Biomarker and Therapeutic Target - Nelson S. Yee (MDPI AG, 2017)
The transient receptor potential melastatin-subfamily member 7 (TRPM7) is a ubiquitously expressed ion channel with intrinsic kinase activity. Molecular and electrophysiological analyses of the structure and activity of TRPM7 have revealed functional coupling of its channel and kinase activity. Studies have indicated the important roles of TRPM7 channel-kinase in fundamental cellular processes, physiological responses, and embryonic development. Accumulating evidence has shown that TRPM7 is aberrantly expressed and/or activated in human diseases including cancer. TRPM7 plays a variety of functional roles in cancer cells including survival, cell cycle progression, proliferation, growth, migration, invasion, and epithelial-mesenchymal transition (EMT). Data from a study using mouse xenograft of human cancer show that TRPM7 is required for tumor growth and metastasis. The aberrant expression of TRPM7 and its genetic mutations/polymorphisms have been identified in various types of carcinoma. Chemical modulators of TRPM7 channel produced inhibition of proliferation, growth, migration, invasion, invadosome formation, and markers of EMT in cancer cells. Taken together, these studies suggest the potential value of exploiting TRPM7 channel-kinase as a molecular biomarker and therapeutic target in human malignancies.